2011
DOI: 10.2135/cropsci2010.10.0598
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Grass–Legume Management

Abstract: A 2-yr grazing study quantified pasture and animal responses of four forage systems (FS) grazed at two stocking rates (SR; 3 or 6 animals ha -1 ). Using "Marshall"annual ryegrass (Lolium multiflorum Lam.) and "Durana" white clover (Trifolium repens

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 90 publications
3
20
0
Order By: Relevance
“…Moreover, considering that in this type of pasture A. pintoi is overlapped by the leaves of elephant grass, future work should be conducted to test spatial distributions that facilitate the legume grazing. This proposition is in accordance with a recent paper published by Solomon et al (2011), which suggest that spatially separated monoculture of grasses and legumes within the same paddock may be an option to enhance adoption of legumes in temperate pastures.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, considering that in this type of pasture A. pintoi is overlapped by the leaves of elephant grass, future work should be conducted to test spatial distributions that facilitate the legume grazing. This proposition is in accordance with a recent paper published by Solomon et al (2011), which suggest that spatially separated monoculture of grasses and legumes within the same paddock may be an option to enhance adoption of legumes in temperate pastures.…”
Section: Discussionsupporting
confidence: 92%
“…E-mail: joanna.sharp@plantandfood.co.nz Champion et al, 2004). Furthermore, several studies with sheep, cows and beef have shown livestock production per head is greater when stock graze spatially separated swards than when they graze mixed swards Rutter et al, 2003;Solomon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the growth distributions for these clovers differed, with red clover having a high proportion at the beginning of the 3‐yr study and decreasing as time progressed, whereas white clover had a low proportion at the beginning and increased as the study progressed. Solomon et al (2011) observed white clover proportion in a mixture with annual ryegrass of 230 and 130 g kg −1 at high (6 heads ha −1 ) and low (3 heads ha −1 ) stocking densities, respectively, under continuous stocking. Clover proportion in the current study was generally less than reported in these studies, which may reflect the use of perennial or biennial clovers in the northern regions of the United States or Canada, where weather conditions are more conducive to clover production (Deak et al, 2007; Kunelius and Narasimhalu, 1983; Sanderson et al, 2005; Solomon et al, 2011).…”
Section: Resultsmentioning
confidence: 99%